Validation of an all‐sky imager–based nowcasting system for industrial PV plants. (20th November 2017) - Kuhn, Pascal; Nouri, Bijan; Wilbert, Stefan; Prahl, Christoph; Kozonek, Nora; Schmidt, Thomas; Yasser, Zeyad; Ramirez, Lourdes; Zarzalejo, Luis; Meyer, Angela; Vuilleumier, Laurent; Heinemann, Detlev; et al.
Abstract: Because of the cloud‐induced variability of the solar resource, the growing contributions of photovoltaic plants to the overall power generation challenges the stability of electricity grids. To avoid blackouts, administrations started to define maximum negative ramp rates. Storages can be used to reduce the occurring ramps. Their required capacity, durability, and costs can be optimized by nowcasting systems. Nowcasting systems use the input of upward‐facing cameras to predict future irradiances. Previously, many nowcasting systems were developed and validated. However, these validations did not consider aggregation effects, which are present in industrial‐sized power plants. In this paper, we present the validation of nowcasted global horizontal irradiance (GHI) and direct normal irradiance maps derived from an example system consisting of 4 all‐sky cameras ("WobaS‐4cam"). The WobaS‐4cam system is operational at 2 solar energy research centers and at a commercial 50‐MW solar power plant. Besides its validation on 30 days, the working principle is briefly explained. The forecasting deviations are investigated with a focus on temporal and spatial aggregation effects. The validation found that spatial and temporal aggregations significantly improve forecast accuracies: Spatial aggregation reduces the relative root mean square error (GHI) from 30.9% (considering field sizes of 25 m 2 ) to 23.5% (considering a field size of 4 km 2 ) on a day with variable conditions for 1 minute averages and a lead time of 15 minutes. Over 30 days of validation, a relative root mean square error (GHI) of 20.4% for the next 15 minutes is observed at pixel basis (25 m 2 ). Although the deviations of nowcasting systems strongly depend on the validation period and the specific weather conditions, the WobaS‐4cam system is considered to be at least state of the art. Abstract : The 4 all‐sky imager–based WobaS nowcasting system is presented and validated with special focus on spatial and temporal aggregation effects on 30 days. General validation principles for nowcasting systems are derived. The WobaS system is at least state of the art.